Letter to the editor concerning the article "Performance of gymnastics skill benefits from an external focus of attention" by Abdollahipour, Wulf, Psotta & Nieto (2015) - Collins, D.; Carson, H. J.; Toner, J. (Journal of Sports Sciences, 2016)
Abdollahipour, Wulf, Psotta, and Nieto (2015) recently published data in the Journal of Sports Sciences to show that an external focus of attention promotes superior performance effects (gymnastics jump height and judged movement form score) when compared to internal or control foci during skill execution without an implement involved. While we do not contest the veracity of findings reported, nor others that have been used to support beneficial effects of an external focus of attention, in this Letter to the Editor we comment on considerable methodological limitations associated with this and previous studies that, we suggest, have resulted in serious theoretical oversights regarding the control of movement and, most crucially from our practitioner perspective, suboptimal recommendations for applied coaching practice. Specifically, we discuss the lack of consideration towards translational research in this area, the problematic nature of attentional focus cues employed, interpretation of findings in relation to other applied recommendations and coherence with mechanistic underpinning and, finally, the representative nature of task involved. In summary, while (laboratory) research evidence may appear to be conclusive, we suggest that the focus of attention effects are in need of more ecologically valid and rigorous testing as well as consideration of current coaching practices if it is to optimally serve the applied sporting domain that it purportedly aims to.